2019
DOI: 10.3389/fmicb.2019.01598
|View full text |Cite
|
Sign up to set email alerts
|

B-1 Cells May Drive Macrophages Susceptibility to Trypanosoma cruzi Infection

Abstract: B-1 cells can directly and indirectly influence the immune response. These cells are known to be excellent producers of natural antibodies and can secrete a variety of immunomodulatory molecules. They are also able to differentiate into B-1 cell-derived phagocytes (B-1CDP). B-1 cells can modulate macrophages to become less effective, and B-1CDP cells are more susceptible in infection models. In this work, we investigated the microbicidal ability of these cells in Trypanosoma cruzi infection in vitro. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The trypomastigote forms when phagocytosed by macrophages differ from amastigote forms, with the macrophage state being the determinant for their survival. IFN-γ-activated macrophages are able to partially destroy the parasites [44,45,66,67]. The results obtained in our study corroborate the previous studies since the presence of collagen I did not alter the activation of the macrophages by IFN-γ and LPS, which still were able to control the intracellular replication of T. cruzi [68].…”
Section: Discussionsupporting
confidence: 90%
“…The trypomastigote forms when phagocytosed by macrophages differ from amastigote forms, with the macrophage state being the determinant for their survival. IFN-γ-activated macrophages are able to partially destroy the parasites [44,45,66,67]. The results obtained in our study corroborate the previous studies since the presence of collagen I did not alter the activation of the macrophages by IFN-γ and LPS, which still were able to control the intracellular replication of T. cruzi [68].…”
Section: Discussionsupporting
confidence: 90%
“…Studies using B-1 cells of deficient mice (XID mice), suggested an important role for these cells during the immune responses against infections 29 , 30 , 34 , 35 . This led us to investigate if the B-1 cells would be implyed in the response against C. gattii infection on this animal model.…”
Section: Resultsmentioning
confidence: 99%
“…The role of B-1 lymphocytes in antibody production has been characterized. However, these cells also have other characteristics that can play important mechanisms in protecting against different pathogens, and one of these mechanisms is their ability to differentiate into phagocytes called B-1 cell-derived phagocytes (B-1CDP) 30 , 34 , 72 74 . It was also shown that B-1 cells migrate to the inflammatory/infectious focus and differentiate into macrophage-like cells 75 .…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, higher NO levels were observed in C57BL/6 mice during acute infection with T. cruzi , and iNOS KO mice showed a higher susceptibility to T. cruzi ( Holscher et al., 1998 ). Furthermore, insufficient NO causes a higher susceptibility to T. cruzi in BALB/c mice than in XID mice, which is negatively related to excessive IL-10 secreted by B-1 cells ( da Rocha et al., 2019 ). In addition, parasite-specific IgG and sex differences are also involved in parasite-host adaptation, but further investigation of the underlying mechanisms is needed ( Perez et al., 2005 ; Micucci et al., 2010 ).…”
Section: Main Textmentioning
confidence: 99%